2018
DOI: 10.1002/cncr.31409
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of patients with hematologic malignancies receiving chemotherapy in the intensive care unit

Abstract: Short-term mortality was similar among patients with hematologic malignancies who did and did not receive chemotherapy in the ICU, although patients who received chemotherapy had increased resource utilization. These results may inform ICU triage and goals-of-care discussions with patients and their families regarding outcomes after receiving chemotherapy in the ICU. Cancer 2018;124:3025-36. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(66 reference statements)
0
12
0
1
Order By: Relevance
“…Although our data did not capture remission status of the included patients, we found that active malignancy treatment in the form of chemotherapy and/or radiation is associated with a lower risk of in-hospital mortality among hematologic oncology patients. Following ICU admission, ongoing chemotherapy has been associated with longer length of hospital and ICU stays, but mortality in these patients is similar to those who do not receive chemotherapy [50]. In our study, the association between active treatment and reduced mortality may be influenced by residual confounding, as those who receive active treatment may be healthier and may therefore experience more favorable outcomes following ICU admission.…”
Section: Discussionmentioning
confidence: 75%
“…Although our data did not capture remission status of the included patients, we found that active malignancy treatment in the form of chemotherapy and/or radiation is associated with a lower risk of in-hospital mortality among hematologic oncology patients. Following ICU admission, ongoing chemotherapy has been associated with longer length of hospital and ICU stays, but mortality in these patients is similar to those who do not receive chemotherapy [50]. In our study, the association between active treatment and reduced mortality may be influenced by residual confounding, as those who receive active treatment may be healthier and may therefore experience more favorable outcomes following ICU admission.…”
Section: Discussionmentioning
confidence: 75%
“…Our study also confirms that oncologic emergencies remain the most frequent reason for initiation oncologic therapies for patients with hematologic malignancies. 2,4,5…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described the background methods for this study. 5,6 In brief, using hospital-wide and ICU databases, we identified all ICU patients with cancer who received oncologic therapies. We included for analysis only the first ICU admission during which the patient received oncologic therapies.…”
Section: Methodsmentioning
confidence: 99%
“…Lung cancer and acute respiratory failure due to airway compression or pulmonary infiltrates may explain the high mortality rates[ 182 - 184 ]. In patients with hematological malignancy 25%-40% die in the ICU; 30-d, 6-mo and 1-year mortality rates is 40%, 51%-77% and 50%, respectively[ 10 , 185 ]. Risk factors for mortality are degree of organ dysfunction and life-support methods such as ventilatory support, vasopressors, and renal replacement therapy.…”
Section: Chemotherapy In Icumentioning
confidence: 99%